Association of leptin with food cue-induced activation in human reward pathways - Großhans, Martin; Vollmert, Christian; Vollstädt-Klein, Sabine; Tost, Heike; Leber, Saskia Anna; Bach, Patrick; Fauth-Bühler, Mira; Goltz, Christoph von der; Mutschler, Jochen; Steins-Löber, Sabine; Hermann, Derik; Wiedemann, Klaus; et al. (Archives of general psychiatry, 2012)
Context: Overlapping neurobiological pathways between obesity and addiction disorders are currently in discussion. Whereas the hypothalamic regulation of energy homeostasis by endocrine feedback signals has been widely investigated, its interplay with mesolimbic reward-associated pathways represents a rich field of future research. Objective: To assess changes in regional brain activation in response to food-related cues in association with body mass index (BMI; calculated as weight in kilograms divided by height in meters squared) and the plasma concentration of the appetite-regulating peptide leptin. Design: Case-control study. Setting: Academic addiction and brain imaging center, Central Institute of Mental Health, Mannheim, Germany. Participants: Twenty-one obese subjects (BMI >30) and 23 age- and sex-matched nonobese control subjects (BMI 18.5-24.0) recruited by advertisements. Main Outcome Measures: Regional brain activation (blood oxygen level–dependent response) in response to visual cue presentation and association of the brain activation with BMI and plasma leptin concentration. Results: Significant positive relationships were observed for food cue–induced brain activations in the ventral striatum in association with the plasma concentration of leptin (r = 0.27; P = .04) and with BMI (r = 0.47; P = .001). Conclusions: Data suggest a physiological role of satiety factors in modulating the responsivity of mesolimbic circuits to food cues. Moreover, an altered homeostatic feedback regulation of reward pathways might explain addictionlike behavior and the inability of obese patients to adapt food intake to physiological needs.
Gesehen am 25.04.2018